Lorenzo Milani's Thought and the Present Italian School Crisis - Lo Monte, Tommaso (INSTED: Interdisciplinary Studies in Education & Society, 2022)
Presently, the Italian school system is in the midst of a profound crisis. The aim of this article is to attempt to find a solution to some of the problems with the aid of Lorenzo Milani’s ideas. The scientific pedagogic method used is based on the analysis of all Milani’s publications, which were recently peer-reviewed. Contrary to other published studies, this article will focus on the link between the Italian school system and Milani’s analysis of society, drawing attention to the responsibility of the teachers who are, in fact, the instruments by which society has perpetuated the existing oppressive system. According to Milani, the school’s role should consist of giving the students all the necessary instruments to become an integral part of a democratic society. Thanks to Milani’s analysis of society and the school system, it would be possible to offer a solution to the crisis from its “core” origin. In other words, beginning with the responsibility of the teachers, the only ones capable of changing the status quo.